2000
DOI: 10.1016/s0163-8343(00)00102-x
|View full text |Cite
|
Sign up to set email alerts
|

Panic disorder among Cambodian refugees attending a psychiatric clinic

Abstract: This study surveys Khmer refugees attending two psychiatric clinics to determine both the prevalence of panic disorder as well as panic attack subtypes in those suffering panic disorder. A culturally valid adaptation of the SCID-panic module, the Cambodian Panic Disorder Survey (CPDS), was administered to 89 consecutive Cambodian refugees attending these psychiatric clinics. Utilizing culturally sensitive panic probes, the CPDS provides information regarding both the presence of panic disorder and panic-attack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 60 publications
(49 reference statements)
0
76
0
Order By: Relevance
“…Of note, as in a survey of Khmer patients [23], during the panic attacks subtypes assessed by the special probes (e.g., headache and orthostatically induced dysphoria), almost all patients feared death and were highly distressed.…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…Of note, as in a survey of Khmer patients [23], during the panic attacks subtypes assessed by the special probes (e.g., headache and orthostatically induced dysphoria), almost all patients feared death and were highly distressed.…”
Section: Resultsmentioning
confidence: 86%
“…Furthermore, as a supplement, to provide comparative data to the survey of Cambodian refugees [23], four more probes were utilized, though from clinical experience the author doubted a positive reply would be found in the Vietnamese population: sore-neck dysphoria; hunger-induced distress; olfactory-triggered dysphoria; and head turning or seeing spinning objects as causing distress. In regard to this last query, in the Khmer survey [23], it was found that 16% of the panic disorder patients suffered "while-sitting dizziness."…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations